Nursing Students' Perceptions and Attitudes about Altruism - Shanti Wardaningsih; Intansari Adiningrum (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The current trend of globalization allows a person to be lazy to socialize, thereby reducing one's altruism. In this case, college students have an essential role in applying altruism as a professional value of nursing. Altruism is a principle of caring to realize the welfare of other people's lives with sincerity without expecting anything in return. This study used a qualitative method with a descriptive approach. Data were collected through online interviews utilizing Zoom and Ms. Teams. Participants in this study amounted to seven people selected by the purposive sampling method. The data validity employed credibility, transferability, dependability, and confirmability tests. The results of this study revealed that the perceptions and attitudes of nursing students about altruism included altruism making a person better, altruism as a form of responsibility, altruism as a religious and social value, factors confirming altruism, and factors driving altruism. Here, nursing students must have altruistic behavior as a form of responsibility and its application to social and religious values. In addition, behaving altruistically provides many positive benefits for both helpers and those being helped. Suggestions for further research are the need for further action related to the results of this study to identify factors that can increase altruism behavior so that it can be used as a reference to improve nursing student altruism behavior. Abstrak: Tren globalisasi saat ini memungkinkan seseorang menjadi malas untuk bersosialisasi sehingga menurunkan sifat altruisme seseorang. Mahasiswa memiliki peran penting untuk menerapkan altruisme sebagai nilai profesional keperawatan. Altruisme merupakan suatu prinsip kepedulian untuk mewujudkan kesejahteraan hidup orang lain dengan keikhlasan tanpa mengharapkan suatu imbalan. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Pengambilan data dilakukan dengan wawancara secara online melalui Zoom dan Ms Teams. Partisipan dalam penelitian ini berjumlah 7 orang yang dipilih dengan metode purposive sampling. Keabsahan data menggunakan uji credibility, transferability, dependability, confirmability. Hasil penelitian ini menunjukan persepsi dan sikap mahasiswa keperawatan tentang altruisme yaitu meliputi altruisme menjadikan seseorang lebih baik, altruisme sebagai bentuk tanggungjawab, altruisme sebagai nilai agama dan sosial, faktor yang meneguhkan altruisme, serta faktor yang menggerakan altruisme. Mahasiswa keperawatan penting untuk memiliki perilaku altruisme sebagai bentuk tanggung jawab dan juga penerapannya sebagai nilai sosial dan agama. Berperilaku altruisme memberikan banyak manfaat positif bagi penolong maupun yang ditolong. Saran untuk peneliti selanjutnya yaitu perlu adanya tindakan lanjut terkait hasil penelitian ini untuk mengidentifikasi faktor-faktor yang dapat meningkatkan perilaku altruisme sehingga dapat dijadikan sebagai acuan untuk meningkatkan perilaku altruisme mahasiswa keperawatan.